Analisis Manajemen Pengangkutan TBS di PT. Serba Huta Jaya Desa Sumber Mulyo, Kecamatan Marbau, Kabupaten Labuhanbatu Utara, Sumatera Utara - Putri, Cindy Camellya; Listiyani; Dewi, Christina Wahyu Ary (Program Studi Agribisnis INSTIPER Yogyakarta, 2024)
This research aims to determine the management of transporting fresh palm fruit bunches (FFB) at PT. Serba Huta Jaya, analyzed the performance of transporting FFB from the harvesting site (TPH) to the palm oil mill (PKS), analyzing the obstacles in transporting FFB from TPH to PKS. The research method used in this research is mixed methods. According to Sugiyono (2015), mixed research methods are a research method between quantitative methods and qualitative methods to be used together in a research activity, so that more comprehensive, valid, reliable and objective data is obtained. The sample in this study was 10 FFB transport drivers and 20 loading and unloading workers. The results of this research indicate that FFB transportation management at PT. Serba Huta Jaya is still not doing well because there are frequent delays in FFB deliveries resulting in fruit being left on the trucks. There are several things that must be considered, namely road access for transporting FFB, the speed of harvest employees in cutting fruit, and damage to trucks in the field. The average performance of transporting FFB from TPH to PKS is 2.08 tonnes/hour and the average cost for one transport is Rp. 62.96/kg. The obstacles faced when transporting fruit from TPH to PKS were that the roads were still damaged at several points and the trucks were damaged while in the field.